Method for polarizing plate moisture absorption test and quick recovery

By covering the polarizer with a clean cloth and baking it at high temperature, the problem of long recovery time in the moisture absorption test was solved, and rapid and accurate testing and optical performance recovery were achieved.

CN123046002APending Publication Date: 2026-11-06SHENZHEN SAPO PHOTOELECTRIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611249825.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

In existing technologies, the hygroscopicity test of polarizers requires 2-3 months to recover, which is inefficient and cannot meet the need for rapid recovery.

Method used

The polarizer was covered with a lint-free cloth and a release film to prevent moisture evaporation. After standing for 72 hours, the color difference was observed. Then, it was baked in a high-temperature environment of 40℃~70℃ for 1 hour. The whitening phenomenon was observed to disappear, and the optical performance was tested.

Benefits of technology

It achieves rapid and accurate testing of the hygroscopicity of polarizers, shortens the recovery time to 1 hour, ensures the recovery of optical performance, and improves testing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123046002A_ABST
    Figure CN123046002A_ABST
Patent Text Reader

Abstract

The application discloses a kind of polarizing sheet hygroscopicity test and the method of quick recovery, comprising the following steps: step S1, hygroscopicity test: wet dustless cloth is covered in the surface of the to-be-tested area of polarizing sheet, and covers release film on the dustless cloth to prevent water evaporation, rest for more than 72h, observe the color difference of the covered position and the uncovered position of the dustless cloth, judge the hygroscopicity of polarizing sheet according to whether whitening phenomenon appears and whitening degree;Step S2, recovery: polarizing sheet after hygroscopicity test of step S1 is placed in 40~70 DEG C environment and is baked for more than 1h, observe whether whitening phenomenon of abnormal position disappears.The technical scheme of the application, method is simple, strong operability, can accurately judge the hygroscopicity of polarizing sheet, can make color after hygroscopicity recovery, can also guarantee the optical performance of product, greatly improve efficiency, with good industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polarizer production and testing technology, and in particular to a method for testing and rapidly recovering moisture absorption in polarizers. Background Technology

[0002] A polarizer, also known as a light polarizer, is essential for liquid crystal displays (LCDs) to form images. All LCDs have two polarizers, one on the front and one on the back, bonded to the liquid crystal glass, forming a liquid crystal sheet with a total thickness of approximately 1mm. Without either polarizer, the liquid crystal sheet cannot display an image. Currently, LCD technology is mature and has a wide range of applications, including televisions, commercial displays, laptops, PC monitors, smartphones, and tablets. In recent years, its application in automotive displays, wearable technology, and electronic tags has also been expanding, leading to increasing market demand.

[0003] The basic structure of a polarizer includes: a PVA (polyvinyl alcohol) film in the center, which polarizes light; TAC (cellulose triacetate) films on both sides of the polarizer, which protect it; a protective film on the upper TAC film; and PSA (acrylic adhesive) and a release film on the lower TAC film. Because PVA film is highly absorbent, a layer of TAC film with high transmittance, good water resistance, and a certain mechanical strength is laminated on both sides of the PVA film to protect the physical properties of the polarizer, forming the polarizer base plate.

[0004] The performance of polarizers mainly includes optical performance and durability. Optical performance mainly refers to the polarization degree, single-element transmittance, hue b-value, haze, and reflectivity of the polarizer; durability includes resistance to high temperature, high temperature and high humidity, low temperature, and thermal shock.

[0005] Currently, the main durability tests for polarizers include high temperature resistance, high temperature and high humidity resistance, low temperature resistance, and thermal shock resistance. With the increasing diversity of polarizer usage environments and transportation conditions, the performance requirements for polarizers are becoming more stringent, and the number of testing conditions is also increasing. Among these, the moisture absorption of polarizers is a mandatory test required by customers.

[0006] The hygroscopicity of polarizers primarily assesses the water-blocking capability of the protective layer on the polarizer, with higher water-blocking performance being better. Since water absorption mainly occurs in the upper protective layer, it is difficult for it to penetrate the PVA film layer. As the PVA film remains undamaged, it can recover after absorbing moisture. Generally, polarizers that have absorbed moisture require 2 to 3 months of exposure to normal temperature and humidity (25℃±5℃, 55%RH±10%RH) to recover. This method is time-consuming and inefficient.

[0007] Therefore, it is necessary to develop a method for testing and rapidly recovering the moisture absorption of polarizers to overcome the shortcomings of existing technologies. Summary of the Invention

[0008] To address the above technical problems, this invention discloses a method for testing and rapidly restoring the moisture absorption performance of a polarizer. This method can quickly and accurately determine the moisture absorption performance of a polarizer and restore it to its normal state within a short time. It overcomes the shortcomings of existing technologies where the recovery time after moisture absorption testing is as long as 2-3 months and the efficiency is low.

[0009] The technical solution adopted by this invention is as follows:

[0010] A method for testing and rapidly recovering the moisture absorption of a polarizer includes the following steps:

[0011] Step S1, Moisture Absorption Test: Cover the test area of ​​the polarizer with a damp cleanroom cloth, and cover the cleanroom cloth with a release film to prevent moisture evaporation. Let it stand for more than 72 hours, and observe the color difference between the covered and uncovered areas. The moisture absorption performance of the polarizer is judged based on whether whitening occurs and the degree of whitening.

[0012] Step S2, Recovery: Place the polarizer that has undergone the moisture absorption test in step S1 in an environment of 40℃~70℃ for baking for more than 1 hour, and observe whether the whitening phenomenon in the abnormal position disappears.

[0013] This technical solution involves covering a polarizing film with a cleanroom cloth containing a certain amount of water, and then covering it with a release film to prevent moisture evaporation. After standing for a period of time, the color difference between the area covered by the cleanroom cloth and the normal area of ​​the polarizing film is observed. A "whitening" phenomenon will appear after moisture absorption. The presence and degree of whitening indicate the difference in the moisture absorption performance of the polarizing film. This method is simple, easy to operate, and can accurately determine the moisture absorption performance of the polarizing film.

[0014] By immersing the polarizer after moisture absorption testing in a high-temperature aging chamber (preferably 40°C) for baking, and then observing it, the "whitening" effect after moisture absorption disappears. Further testing of its optical performance, such as single-element transmittance, degree of polarization, hue b-value, haze, and reflectivity, shows that these properties are at the same level as in the normal position. This method not only restores the color after moisture absorption but also ensures the product's optical performance, providing a rapid recovery method for polarizers that have absorbed water due to environmental factors.

[0015] As a further improvement of the present invention, in step S1, the amount of water used for wetting the cleanroom cloth per unit area is 320-340 mL / m². 2 .

[0016] As a further improvement of the present invention, in step S1, the size of the cleanroom cloth is 110mm×110mm, and the amount of water used to wet the cleanroom cloth is 4ml.

[0017] As a further improvement of the present invention, in step S1, the cleanroom cloth covers the corner area of ​​the polarizer, and the cleanroom cloth is at least 20mm away from the edge of the polarizer.

[0018] As a further improvement of the present invention, in step S2, the temperature of the high-temperature environment is 40°C to 60°C.

[0019] As a further improvement of the present invention, in step S2, the baking temperature is 40°C.

[0020] As a further improvement of the present invention, in step S2, the baking time is 1 hour.

[0021] As a further improvement of the present invention, the method for testing the moisture absorption of the polarizer and its rapid recovery further includes: step S3, performing optical performance tests on the whitened position and the normal position of the polarizer after step S2, wherein the optical performance tests include at least one of the following: single-element transmittance test, polarization degree test, hue b-value test, reflectance test and haze test.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] The technical solution of this invention involves covering a polarizer with a clean, dry cloth containing a certain amount of water, then covering it with a release film to prevent moisture evaporation. After standing, the color difference between the covered area and the normal area of ​​the polarizer is observed. A whitening phenomenon will appear after moisture absorption, which indicates the difference in the polarizer's moisture absorption performance. This method is simple, easy to operate, and can accurately determine the moisture absorption performance of the polarizer. Furthermore, by placing the polarizer after the moisture absorption test in a high-temperature aging chamber for 1 hour, the whitening disappears, and its optical performance—monomer transmittance, degree of polarization, hue b-value, haze, and reflectivity—is tested and found to be at the same level as the normal area. This method can restore the color after moisture absorption while ensuring the product's optical performance, providing a rapid recovery method for polarizers that have absorbed water due to environmental factors. Compared with existing recovery methods that require 2-3 months of storage at room temperature and humidity, the technical solution of this invention can shorten the recovery time to 1 hour, significantly improving efficiency and possessing good industrial application value. Attached Figure Description

[0024] Figure 1The figures show the test results of reflectivity before baking in Examples 1 to 5 of this invention. In the figures, 30-before-baking-normal refers to the reflectivity before baking in the normal position of Example 1, 40-before-baking-normal refers to the reflectivity before baking in the normal position of Example 2, 50-before-baking-normal refers to the reflectivity before baking in the normal position of Example 3, 60-before-baking-normal refers to the reflectivity before baking in the normal position of Example 4, and 70-before-baking-normal refers to the reflectivity before baking in the normal position of Example 5; 30-before-baking-abnormal refers to the reflectivity before baking in the abnormal position of Example 1, 40-before-baking-abnormal refers to the reflectivity before baking in the abnormal position of Example 2, 50-before-baking-abnormal refers to the reflectivity before baking in the abnormal position of Example 3, 60-before-baking-abnormal refers to the reflectivity before baking in the abnormal position of Example 4, and 70-before-baking-abnormal refers to the reflectivity before baking in the abnormal position of Example 5.

[0025] Figure 2 The figures show the test results of reflectivity after drying in Examples 1 to 5 of this invention. In the figures, 30-after-drying-normal refers to the reflectivity after drying in the normal position in Example 1, 40-after-drying-normal refers to the reflectivity after drying in the normal position in Example 2, 50-after-drying-normal refers to the reflectivity after drying in the normal position in Example 3, 60-after-drying-normal refers to the reflectivity after drying in the normal position in Example 4, and 70-after-drying-normal refers to the reflectivity after drying in the normal position in Example 5; 30-after-drying-abnormal refers to the reflectivity after drying in the abnormal position in Example 1, 40-after-drying-abnormal refers to the reflectivity after drying in the abnormal position in Example 2, 50-after-drying-abnormal refers to the reflectivity after drying in the abnormal position in Example 3, 60-after-drying-abnormal refers to the reflectivity after drying in the abnormal position in Example 4, and 70-after-drying-abnormal refers to the reflectivity after drying in the abnormal position in Example 5.

[0026] Figure 3 The figures show the test results of monomer transmittance before baking in Examples 1 to 5 of the present invention. In the figures, 30-before-baking-normal refers to the monomer transmittance before baking in the normal position of Example 1, 40-before-baking-normal refers to the monomer transmittance before baking in the normal position of Example 2, 50-before-baking-normal refers to the monomer transmittance before baking in the normal position of Example 3, 60-before-baking-normal refers to the monomer transmittance before baking in the normal position of Example 4, and 70-before-baking-normal refers to the monomer transmittance before baking in the normal position of Example 5; 30-before-baking-abnormal refers to the monomer transmittance before baking in the abnormal position of Example 1, 40-before-baking-abnormal refers to the monomer transmittance before baking in the abnormal position of Example 2, 50-before-baking-abnormal refers to the monomer transmittance before baking in the abnormal position of Example 3, 60-before-baking-abnormal refers to the monomer transmittance before baking in the abnormal position of Example 4, and 70-before-baking-abnormal refers to the monomer transmittance before baking in the abnormal position of Example 5.

[0027] Figure 4The figures show the test results of monomer permeability after baking in Examples 1 to 5 of this invention. In the figures, 30-after-baking-normal refers to the monomer permeability after baking in the normal position in Example 1, 40-after-baking-normal refers to the monomer permeability after baking in the normal position in Example 2, 50-after-baking-normal refers to the monomer permeability after baking in the normal position in Example 3, 60-after-baking-normal refers to the monomer permeability after baking in the normal position in Example 4, and 70-after-baking-normal refers to the monomer permeability after baking in the normal position in Example 5; 30-after-baking-abnormal refers to the monomer permeability after baking in the abnormal position in Example 1, 40-after-baking-abnormal refers to the monomer permeability after baking in the abnormal position in Example 2, 50-after-baking-abnormal refers to the monomer permeability after baking in the abnormal position in Example 3, 60-after-baking-abnormal refers to the monomer permeability after baking in the abnormal position in Example 4, and 70-after-baking-abnormal refers to the monomer permeability after baking in the abnormal position in Example 5. Detailed Implementation

[0028] The preferred embodiments of the present invention will be described in further detail below.

[0029] A method for testing and rapidly recovering the moisture absorption of a polarizer includes the following steps:

[0030] 1) Moisture Absorption Test Method

[0031] ① Sample preparation: Cut the polarizer to a suitable size, preferably 710mm×406mm; cut the cleanroom cloth to a suitable size, preferably 110mm×110mm.

[0032] ② Moistening the cleanroom cloth: Moisten the cut cleanroom cloth, preferably 110mm×110mm in size, with 4ml of purified water.

[0033] ③ Cover with cleanroom cloths: Remove the protective film from the polarizer and cover the four corners of the polarizer with three damp cleanroom cloths, keeping the cleanroom cloths at least 20mm away from the edge of the polarizer.

[0034] ④ Polarizing film moisture absorption test: Cover a damp cleanroom cloth with a release film to prevent moisture evaporation and let it stand for 72 hours. After 72 hours, observe the color difference between the covered area and the normal area. "Whitening" indicates that the polarizing film protective layer has absorbed water.

[0035] 2) Recovery Method

[0036] ① Place the water-absorbing polarizer into a high-temperature environment chamber and bake it for a period of time. Observe whether the "whitening" in the abnormal area disappears.

[0037] 3) Characteristic value testing

[0038] ① Optical performance test: The polarizer taken out of the high temperature chamber was tested with a JASCO V-7100 spectrophotometer for optical performance at the "whitening position" and normal position, and the data was recorded and compared with the optical performance at the "whitening position" and normal position.

[0039] ②Reflectance performance test: The polarizer taken out of the high temperature chamber was tested with a UV2600 spectrophotometer for the reflectance of the "whitened position" and the normal position, and the data was recorded to compare the reflectance performance of the "whitened position" and the normal position.

[0040] ③ Haze performance test: The polarizer taken out of the high temperature chamber was tested with an NDH5000 haze meter at the “whitening position” and the normal position, and the data was recorded and compared with the haze values ​​at the “whitening position” and the normal position.

[0041] The following detailed description is based on specific embodiments.

[0042] Example 1

[0043] ① Sample preparation: Cut the polarizing film to 710mm×406mm; cut the cleanroom cloth to 110mm×110mm.

[0044] ② Moistening the cleanroom cloth: Moisten the cut cleanroom cloth with 4ml of purified water.

[0045] ③ Cover with cleanroom cloths: Remove the protective film from the polarizer and cover the four corner areas of the polarizer with three damp cleanroom cloths, keeping the cleanroom cloths at least 20mm away from the edge of the polarizer.

[0046] ④ Polarizing film moisture absorption test: Cover the damp cleanroom cloth with release film and let it stand for 72 hours. After 72 hours, observe the color difference between the covered area and the normal area.

[0047] ⑤ Moisture absorption and recovery method: Place the polarizer that has absorbed water into a high-temperature environment chamber at 30°C and bake for 1 hour. Observe whether the whitening in the abnormal area disappears.

[0048] ⑥ Characteristic value testing: The optical performance of the whitened and normal positions was tested using a JASCO V-7100 spectrophotometer; the reflectance of the whitened and normal positions was tested using a UV2600 spectrophotometer; and the haze value of the whitened and normal positions was tested using an NDH5000 haze meter. The data were recorded, and the differences in characteristic values ​​between the whitened and normal positions were compared.

[0049] Example 2

[0050] ① Sample preparation: Cut the polarizing film to 710mm×406mm; cut the cleanroom cloth to 110mm×110mm.

[0051] ② Moistening the cleanroom cloth: Moisten the cut cleanroom cloth with 4ml of purified water.

[0052] ③ Cover with cleanroom cloths: Remove the protective film from the polarizer and cover the four corner areas of the polarizer with three damp cleanroom cloths, keeping the cleanroom cloths at least 20mm away from the edge of the polarizer.

[0053] ④ Polarizing film moisture absorption test: Cover the damp cleanroom cloth with release film and let it stand for 72 hours. After 72 hours, observe the color difference between the covered area and the normal area.

[0054] ⑤ Moisture absorption and recovery method: Place the polarizer that has absorbed water into a high-temperature environment chamber at 40°C and bake for 1 hour. Observe whether the whitening in the abnormal area disappears.

[0055] ⑥ Characteristic value testing: The optical performance of the whitened and normal positions was tested using a JASCO V-7100 spectrophotometer; the reflectance of the whitened and normal positions was tested using a UV2600 spectrophotometer; and the haze value of the whitened and normal positions was tested using an NDH5000 haze meter. The data were recorded, and the differences in characteristic values ​​between the whitened and normal positions were compared.

[0056] Example 3

[0057] ① Sample preparation: Cut the polarizing film to 710mm×406mm; cut the cleanroom cloth to 110mm×110mm.

[0058] ② Moistening the cleanroom cloth: Moisten the cut cleanroom cloth with 4ml of purified water.

[0059] ③ Cover with cleanroom cloths: Remove the protective film from the polarizer and cover the four corner areas of the polarizer with three damp cleanroom cloths, keeping the cleanroom cloths at least 20mm away from the edge of the polarizer.

[0060] ④ Polarizing film moisture absorption test: Cover the damp cleanroom cloth with release film and let it stand for 72 hours. After 72 hours, observe the color difference between the covered area and the normal area.

[0061] ⑤ Moisture absorption and recovery method: Place the polarizer that has absorbed water into a high-temperature environment chamber at 50°C and bake for 1 hour. Observe whether the whitening in the abnormal area disappears.

[0062] ⑥ Characteristic value testing: The optical performance of the whitened and normal positions was tested using a JASCO V-7100 spectrophotometer; the reflectance of the whitened and normal positions was tested using a UV2600 spectrophotometer; and the haze value of the whitened and normal positions was tested using an NDH5000 haze meter. The data were recorded, and the differences in characteristic values ​​between the whitened and normal positions were compared.

[0063] Example 4

[0064] ① Sample preparation: Cut the polarizing film to 710mm×406mm; cut the cleanroom cloth to 110mm×110mm.

[0065] ② Moistening the cleanroom cloth: Moisten the cut cleanroom cloth with 4ml of purified water.

[0066] ③ Cover with cleanroom cloths: Remove the protective film from the polarizer and cover the four corner areas of the polarizer with three damp cleanroom cloths, keeping the cleanroom cloths at least 20mm away from the edge of the polarizer.

[0067] ④ Polarizing film moisture absorption test: Cover the damp cleanroom cloth with release film and let it stand for 72 hours. After 72 hours, observe the color difference between the covered area and the normal area.

[0068] ⑤ Moisture absorption and recovery method: Place the polarizer that has absorbed water into a high-temperature environment chamber at 60℃ and bake for 1 hour. Observe whether the whitening in the abnormal area disappears.

[0069] ⑥ Characteristic value testing: The optical performance of the whitened and normal positions was tested using a JASCO V-7100 spectrophotometer; the reflectance of the whitened and normal positions was tested using a UV2600 spectrophotometer; and the haze value of the whitened and normal positions was tested using an NDH5000 haze meter. The data were recorded, and the differences in characteristic values ​​between the whitened and normal positions were compared.

[0070] Example 5

[0071] ① Sample preparation: Cut the polarizing film to 710mm×406mm; cut the cleanroom cloth to 110mm×110mm.

[0072] ② Moistening the cleanroom cloth: Moisten the cut cleanroom cloth with 4ml of purified water.

[0073] ③ Cover with cleanroom cloths: Remove the protective film from the polarizer and cover the four corner areas of the polarizer with three damp cleanroom cloths, keeping the cleanroom cloths at least 20mm away from the edge of the polarizer.

[0074] ④ Polarizing film moisture absorption test: Cover the damp cleanroom cloth with release film and let it stand for 72 hours. After 72 hours, observe the color difference between the covered area and the normal area.

[0075] ⑤ Moisture absorption and recovery method: Put the polarizer that has absorbed water into a high-temperature environment chamber at 70℃ and bake for 1 hour. Observe whether the whitening in the abnormal area disappears.

[0076] ⑥ Characteristic value testing: The optical performance of the whitened and normal positions was tested using a JASCO V-7100 spectrophotometer; the reflectance of the whitened and normal positions was tested using a UV2600 spectrophotometer; and the haze value of the whitened and normal positions was tested using an NDH5000 haze meter. The data were recorded, and the differences in characteristic values ​​between the whitened and normal positions were compared.

[0077] Comparative Example 1

[0078] ① Sample preparation: Cut the polarizing film to 710mm×406mm; cut the cleanroom cloth to 110mm×110mm.

[0079] ② Moistening the cleanroom cloth: Moisten the cut cleanroom cloth with 4ml of purified water.

[0080] ③ Cover with cleanroom cloths: Remove the protective film from the polarizer and cover the four corner areas of the polarizer with three damp cleanroom cloths, keeping the cleanroom cloths at least 20mm away from the edge of the polarizer.

[0081] ④ Polarizing film moisture absorption test: Cover the damp cleanroom cloth with release film and let it stand for 72 hours. After 72 hours, observe the color difference between the covered area and the normal area.

[0082] ⑤ Moisture absorption recovery method: Place the polarizer that has absorbed water in a normal temperature and humidity environment (25℃±5℃, 55%RH±10%RH) for 3 months and observe whether the whitening in the abnormal area disappears.

[0083] ⑥ Characteristic value testing: The optical performance of the whitened and normal positions was tested using a JASCO V-7100 spectrophotometer; the reflectance of the whitened and normal positions was tested using a UV2600 spectrophotometer; and the haze value of the whitened and normal positions was tested using an NDH5000 haze meter. The data were recorded, and the differences in characteristic values ​​between the whitened and normal positions were compared.

[0084] The test results are shown in Tables 1 and 2. According to Tables 1 and 2, after the moisture absorption test, the area covered by the lint-free cloth showed a whitening phenomenon, indicating that the protective layer of the polarizer absorbed water. Based on the characteristic value test results, the main difference between the water-absorbing area (whitening area) and the normal area lies in the monomer transmittance and reflectance. The monomer transmittance decreases and the reflectance increases in the whitening area.

[0085] Table 1. Results of moisture absorption test in normal position before baking

[0086]

[0087] Table 2. Results of the whitish area test before baking in the moisture absorption test.

[0088]

[0089] Evaluation criteria: ◎ No whitening; ○ Whitening present, as shown in Tables 3 and 4.

[0090] The polarizer was baked after absorbing moisture, and the results are shown in Tables 3 and 4. It can be seen that, except at 30℃, the "whitening" phenomenon disappeared at other temperatures, and the hue returned to its normal position, indicating that baking can restore the water-absorbing parts of the polarizer's protective layer. According to the characteristic value test results, except at 30℃, the transmittance increased and the reflectance decreased at other temperatures, returning to levels comparable to the normal position. This indicates that baking at appropriate temperatures not only restores the whitening but also restores the optical performance of the polarizer.

[0091] Baking at 30℃ for 1 hour did not restore the monomer transmittance and reflectance. Baking at 60℃ and 70℃ for 1 hour restored the monomer transmittance and reflectance, but the hue b-value increased significantly compared to before baking, affecting the b-value performance of the polarizer. Baking at 40℃ and 50℃ for 1 hour eliminated the whitening, restored the monomer transmittance and reflectance of the polarizer, and had no significant impact on the b-value of the polarizer. From an energy consumption perspective, baking at 40℃ for 1 hour is the best method for moisture absorption testing.

[0092] Table 3. Results of moisture absorption test in normal position after baking

[0093]

[0094] Table 4. Results of the whitish area test after baking in the moisture absorption test.

[0095]

[0096] The reflectance of the examples and comparative examples was tested, and the results are as follows: Figure 1 and Figure 2 As shown. Figure 1 As shown, the reflectivity increases after the moisture absorption test. Figure 2 As shown, the reflectivity can be restored by baking at a suitable temperature, except at 30℃. This is consistent with the reflectivity results in Tables 1-4 above.

[0097] Monomer transmittance tests were performed on the examples and comparative examples, and the results are as follows: Figure 3 and Figure 4 As shown. Figure 3 As shown, the monomer transmittance decreased after the moisture absorption test. Figure 4 As shown, the monomer transmittance can be recovered by baking at a suitable temperature, except at 30°C. This is consistent with the monomer transmittance results in Tables 1-4 above.

[0098] In summary, based on the above test results: baking at 30℃ for 1 hour does not eliminate the whitening, and reflectivity and monomer transmittance cannot be recovered; baking at 60℃ and 70℃ for 1 hour does eliminate the whitening, and reflectivity and monomer transmittance can be recovered, but hue b-value and polarization degree cannot be recovered; while baking at 40℃ and 50℃ eliminates the whitening, and optical monomer transmittance, reflectivity, polarization degree, and b-value can all be recovered, consistent with the results of the normal temperature and humidity recovery method. From an energy consumption perspective, baking at 40℃ for 1 hour is the best method for rapid recovery in water permeability testing.

[0099] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention.

Claims

1. A method for testing and rapidly recovering the moisture absorption of a polarizer, characterized in that: Includes the following steps: Step S1, Moisture Absorption Test: Cover the test area of ​​the polarizer with a damp cleanroom cloth, and cover the cleanroom cloth with a release film to prevent moisture evaporation. Let it stand for more than 72 hours, and observe the color difference between the covered and uncovered areas. The moisture absorption performance of the polarizer is judged based on whether whitening occurs and the degree of whitening. Step S2, Recovery: Place the polarizer that has undergone the moisture absorption test in step S1 in an environment of 40℃~70℃ for baking for more than 1 hour, and observe whether the whitening phenomenon in the abnormal position disappears.

2. The method for testing and rapidly recovering the moisture absorption of a polarizer according to claim 1, characterized in that: In step S1, the size of the cleanroom cloth is 110mm×110mm, and the amount of water used to wet the cleanroom cloth is 4ml.

3. The method for testing and rapidly recovering the moisture absorption of a polarizer according to claim 1, characterized in that: In step S1, the cleanroom cloth covers the corner area of ​​the polarizer, and the cleanroom cloth is at least 20mm away from the edge of the polarizer.

4. The method for testing and rapidly recovering the moisture absorption of a polarizer according to claim 1, characterized in that: In step S2, the temperature of the high-temperature environment is 40℃~60℃.

5. The method for testing and rapidly recovering the moisture absorption of a polarizer according to claim 4, characterized in that: In step S2, the baking temperature is 40°C.

6. The method for testing and rapidly recovering the moisture absorption of a polarizer according to claim 4, characterized in that: In step S2, the baking process takes 1 hour.

7. The method for testing and rapidly recovering the moisture absorption of a polarizer according to any one of claims 1 to 6, characterized in that: Also includes: Step S3: Perform optical performance tests on the whitened position and the normal position of the polarizer after step S2. The optical performance tests include at least one of the following: single-element transmittance test, polarization degree test, hue b-value test, reflectance test, and haze test.